Mainstreaming Peace Education in Multicultural Schools Yayasan Perguruan Sultan Iskandar Muda Medan and Karang Turi Semarang - Argitha Aricindy; Wasino Wasino; Hamdan Tri Atmaja; Atika Wijaya (International Conference on Science, Education, and Technology, 2023)
Peace Education for non-violence and peace includes training, skills and information geared towards cultivating a culture of peace based on human rights principles. Learning objectives of peace education may include an understanding of the manifestations of violence, the development of capacities to respond constructively to such violence and specialized knowledge of alternatives to violence. Peace education initiates understanding, tolerance, and friendship among all nations, racial or religious groups and furthermore peace education maintains world security. Peace education has five platforms in the education sector, natural sciences, social and human sciences, culture and communication and information, where the main goal is to promote intercultural dialogue in policies and actions with mutual respect so that the education sector platform in practice has the power to create peace education.